Marine Biotoxins and Seafood Poisoning - Costa, Pedro Reis (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Marine biotoxins may pose a threat to the human consumption of seafood and seafood products. The increasing global trade and higher demand for seafood products worldwide represents a challenge for food safety authorities, policy makers, food business operators, and the scientific community, in particular, researchers devoted to environmental sciences, toxicology, and analytical chemistry. In addition, due to changes in climate conditions and technological developments, new and emerging marine toxins are being detected in regions where they were previously unknown. This Special Issue highlight studies aiming to the develop detection methods for marine biotoxins for better understanding the dynamics of accumulation/elimination of marine biotoxins and their effects on marine organisms, as well as toxin exposure studies that aim to evaluate the risks associated with the consumption of contaminated seafood.